ANALYSIS OF MITIGATION OF THE IMPACT OF THE CONSTRUCTION OF THE BITUNG – SERPONG TOLL ROAD ON ENVIRONMENTAL CONDITIONS - Novyangga, Purnama; Tumilar, Randy Eka; Saputra, Rangga (Universitas Dharmawangsa Medan, 2026)
Roads are a major form of infrastructure that plays a vital role in life. Banten Province is connected by several national roads and toll roads. These national roads and toll roads also connect regencies and cities within the region. With the increasing density of road users, congestion is unavoidable, as these national roads and toll roads are used by vehicles both heading to and leaving Banten Province. Current traffic conditions on toll roads are quite dense (saturated), so to overcome congestion, the construction of alternative roads with a higher level of quality and adequate levels of accessibility and mobility is required. The construction of toll road infrastructure, such as the Bitung-Serpong Toll Road, has a significant impact on the environment. This paper aims to analyze the environmental impacts caused by this toll road construction project, including changes in land use, impacts on ecosystems, pollution, and socio-economic impacts. Through this study, it is hoped that recommendations can be provided for mitigating potential negative impacts.